Negotiating Salafi Ideology in Formal Education: A Study of Adaptation and Pragmatism - Abdussyukur (Al-Mudarris, 2026)
This study addresses a significant gap in Islamic education scholarship by examining how Salafi-affiliated educational institutions negotiate ideological tensions within Indonesia’s formal national education system. Using a qualitative-analytical approach grounded in Weber’s pragmatic social action theory, the study investigates the An-Najah Ihya al-Sunnah Foundation in Takengon, Aceh, through interviews and document analysis. The findings reveal three major patterns of ideological negotiation. First, the institution balances pragmatic demands and doctrinal commitments through institutional negotiation, combining purpose-rational actions (market survival and state legitimacy) with value-rational justifications, enabling it to expand to more than 635 students while maintaining its Salafi identity. Second, it employs strategies of selective retention (Salafi doctrine, Arabic honorifics, gender segregation), selective abandonment (non-mandatory veils, beards, and cingkrang trousers), and strategic adaptation (women’s leadership and participation in national ceremonies). Third, these strategies generate a transitional institutional identity, negotiated piety among students, and pedagogical dissonance requiring continuous justification by educators. The study advances Islamic education discourse by moving beyond the binary of resistance versus acculturation and proposing an analytical framework of institutional ideological negotiation. It demonstrates that Salafi schools function as dynamic, pragmatic institutions that continuously adapt to doctrinal, societal, and state demands, offering important implications for curriculum development, teacher professional development, religious moderation, and educational policy.